Question and answer
What is the area of a triangle with a base of 20.3 m and a height of 5.6 m? A. 28.42 m2 B. 56.84 m2 C. 113.68 m2 D. 227.36 m2
A=1/2*b*h 20.3m*5.6m=113.68m^2 113.68/2=56.84 m^2 The answer is B. 56.84 m2
Expert answered|lwilson384|Points 47|
Question
Asked 3/14/2013 1:23:00 PM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Find the length of each side of the triangle given a perimeter of 45 cm
Weegy: Find the length of each side: 45 / 3 = 15 Split the triangle to get two right-angled triangles. The hypotenuse will be a side of the triangle and one of the other sides will be half a side of the triangle. Call the remaining side (the altitude) x. [ Then use pythagoras. x^2 = 15^2 - 7.5^2 x = sqrt(15^2 - 7.5^2) x = sqrt(168.75) x = 12.9903811 etc.. x = 13.0 cm (to 3 significant figures) ] (More)
Question
Expert Answered
Asked 3/14/2013 1:15:31 PM
0 Answers/Comments
Find the perimeter of an equilateral triangle with side length of 12 inches. A. 12 in B. 72 in C. 48 in D. 36 in
Weegy: D. 36 inches (More)
Question
Expert Answered
Asked 3/14/2013 1:26:11 PM
0 Answers/Comments
In the essay "Mother Tongue," why was Amy Tan once ashamed of the way her mother speaks English? A. Because she thought it was rude to speak improper English. B. Because other people often treated her mother poorly because of the way she spoke. C. Because her mother didn't actually care about learning the language. D. Because she had trouble understanding her mother's voice.
Weegy: B. Because other people often treated her mother poorly because of the way she spoke. In the world, all people who speak English as their second language face problems with stereotypes. [ In “Mother Tongue” by Amy Tan she discusses her mother’s own life, and how she coped with her mother’s broken English. Tan was an ashamed of her mother because her poor English, but latter on she became proud of her mother. ] (More)
Question
Expert Answered
Asked 3/14/2013 1:58:37 PM
0 Answers/Comments
18,449,392 questions answered
Popular Conversations
Simplify 12A + 2 + A - 1. 14A - 1 13A - 1 13A + 1 User: ...
Weegy: 12(A - B) = 12A - 12B User: Simplify 10x - 3x + (-5x). -2x 2x 18x -18x Weegy: c.18x User: Simplify ...
11/25/2014 3:05:18 PM| 6 Answers
True or false carbohydrates are made up of carton, hydrogen, and ...
Weegy: The answer is True. Here is the source link: User: The two main types of fiber are?
11/25/2014 7:45:43 PM| 5 Answers
x + y = k x - y = k
Weegy: 8 1/3 - 1 5/6 = 25/3 - 11/6; = 50/6 - 11/6; = 39/6; = 13/2; = 6 1/2 User: 5x + y = 6 5x + 3y = -4 Weegy: ...
11/25/2014 9:09:05 AM| 4 Answers
Determine the solution set of (2x - 5)2 = 11.
Weegy: 2x - 3 = 9 2x = 9 + 3 2x = 12 x = 12/2 x = 6 User: Determine the solution set of (3x + 1)2 - 100 = ...
11/25/2014 11:37:07 AM| 4 Answers
The first English child born in the new world
Weegy: TRUE The first English child born in the new world
11/25/2014 1:29:56 PM| 4 Answers
20,000 pounds equals how many English tons?
11/25/2014 3:30:36 AM| 3 Answers
Simplify 20 + (2 + r). r + 22 22r 20r
Weegy: r + 22 User: Simplify (5a)(5b). 10ab 25ab 55ab Weegy: (5a)(5b) = 25ab User: Simplify 7.95 - 3.86 + ...
11/25/2014 8:53:09 AM| 3 Answers
Which personal pronoun best completes the sentence? How is it used? ...
Weegy: My father made my sister and ME blueberry pancakes for breakfast. The correct pronoun is: me; indirect object. ...
11/25/2014 9:42:28 AM| 3 Answers
t Object]User: y + 3 = 2x y + 4 = 3x If you use the comparison ...
Weegy: 31/8 and 25/8 User: What is the result of adding the system of equations? 2x + y = 4 3x - y = 6 x = 2 x = ...
11/25/2014 10:32:36 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: The correct factored form of the given equation x^2 + 3x - 4 = 0 is (x - 1)(x + 4) = 0. User: olve n3 + 2n2 ...
11/25/2014 11:30:00 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: (x - 3)^2 = 0 written in general form is: x^2 - 6x + 9 = 0 Expand (x - 3)^2 = x^2 - 3x - 3x + 9 = x^2 - 6x + ...
11/25/2014 11:33:47 AM| 3 Answers
Weegy Stuff
S
L
1
L
P
C
1
P
C
1
L
P
C
1
Points 2660 [Total 14370]| Ratings 10| Comments 2560| Invitations 0|Offline
S
L
Points 1435 [Total 3721]| Ratings 0| Comments 1435| Invitations 0|Offline
S
L
Points 777 [Total 1298]| Ratings 6| Comments 717| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
Points 762 [Total 14136]| Ratings 0| Comments 762| Invitations 0|Offline
S
Points 697 [Total 729]| Ratings 1| Comments 687| Invitations 0|Offline
S
1
L
L
Points 273 [Total 6667]| Ratings 0| Comments 273| Invitations 0|Offline
S
L
Points 161 [Total 1457]| Ratings 3| Comments 131| Invitations 0|Online
S
Points 86 [Total 86]| Ratings 1| Comments 76| Invitations 0|Offline
S
Points 50 [Total 50]| Ratings 0| Comments 0| Invitations 5|Offline
S
Points 46 [Total 46]| Ratings 3| Comments 6| Invitations 1|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.